The The Development of Front-end Website for Project Services Monitoring using Scrum Method: A case study at PT. Gerbang Sinergi Prima: A case study at PT. Gerbang Sinergi Prima - Rizky Sampoerna; Eko Darwiyanto; Rio Nurtantyana (Indonesian Journal on Computing (Indo-JC), 2024)
The project service monitoring is one of the essential aspects of a company that ensures all project activities running well. In the current digital transformation era, competition in the digital world makes several companies to used efficient system in their business process, for example the business process at PT. Gerbang Sinergi Prima (GSP). In the prior observation, the project monitoring activities in GSP still use conventional way, which often requires more time and risk like data redundancy. Hence, this study developed a Front-End website for the project service monitoring with Scrum method to emphasize the development process in a complex manner and allow user needs. Differ from the other studies, the system testing used in this study uses the black box and usability testing from four participants with system usability scale (SUS). The results of the black box test showed a perfect score in the result. In addition, the results of testing using SUS got an average score of 63.125 which means this system can be acceptable quite good by users.